Notch3 regulates ferroptosis via ROS‐induced lipid peroxidation in NSCLC cells. Issue 6 (18th March 2022) - Li, Zhikang; Xiao, JinYang; Liu, Mengyu; Cui, Jiaqi; Lian, Bowen; Sun, Yuanlu; Li, Chunyan
Abstract : Ferroptosis is type of programmed cell death, which is known to be involved in certain cancers. Notch3 signaling is reported to be involved in the tumorigenesis of non‐small‐cell lung cancer (NSCLC) and regulates iron metabolism, lipid synthesis, and oxidative stress in some tissues. However, whether Notch3 signaling regulates ferroptosis is unclear. In this study, we found that ferroptosis inhibitors, ferrostatin‐1 and liproxstatin‐1, protected against cell death induced by Notch3 knockdown and that Notch3 knockdown initiated ferroptosis in NSCLC cells by increasing reactive oxygen species (ROS) levels, lipid peroxidation, and Fe 2+ levels, accompanied by downregulation of glutathione peroxidase 4 (GPX4) and peroxiredoxin6 (PRDX6). Conversely, Notch3 intracellular domain overexpression suppressed erastin‐induced ferroptosis, which was synergistically enhanced by MJ33 in H1299 cells via a decrease in ROS levels and lipid peroxidation, accompanied by upregulation of GPX4 and PRDX6. Moreover, Notch3 knockdown decreased tumorigenesis in vivo with downregulation of GPX4 and PRDX6. In summary, here we have identified Notch3 as a potential negative regulator of ferroptosis in NSCLC. Abstract : Notch3 acts as a potential negative regulator of ferroptosis in non‐small‐cell lung cancer. Notch3 knockdown induced ferroptosis as well as downregulation of GPX4 and PRDX 6. Conversely, Notch3 intracellular domain suppresses erastin‐induced ferroptosis synergistically with MJ33. Taken together, our findings provide new insights into a potential strategy for cancer therapy based on targeting Notch3 and ferroptosis.